A importância das palmeiras arborescentes de grande porte na dinâmica das florestas amazônicas sazonalmente secas - Salm, Rodolfo Aureliano (Universidade Federal de São Carlos, 2005)
We investigated and compared the determinants of palm diversity at different spatial scales: along a moisture gradient in a seasonally dry Amazonian forest and using a climatic model comprising the entire Brazilian territory. Climatic hazards seem to strongly determine the distribution of palms, with the relative importance of moisture being highly consistent across scales. A model that represents the importance of large arborescent palms on the dynamics of seasonally dry Amazonian forests was conceived to guide this thesis. Specifically, the model is aimed at guiding the investigation of the role of large arborescent palms on forest regeneration and succession. Aspects of the model were examined with a ecosystem experiment that took advantage of a palm-rich secondary forest patch (=palmeiral) close to the Pinkaití research station, south-eastern Amazon, immersed in a matrix of notably well protected seasonally dry forests, preserved to the purpose of scientific investigation and preservation. We focused on the palms Attalea maripa and Astrocaryum aculeatum, the first naturally abundant and the second rare at the Pinkaití, attempting to establish comparisons between the two species, whenever possible. The Pinkaití, like other seasonally dry forests, have great heterogeneity in forest structure and composition, associated with biotic characteristics of the most important tree species, natural disturbance and history of land-use. The palm grove, moderately dominated by the arborescent palm Attalea maripa (Aubl.) Mart., presented high tree species diversity and was floristically similar to undisturbed forests at the study site. Despite being superficially similar, the palms A. maripa and A. aculeatum are distinct in the structure and development of their stem. The samples of A. maripa stem were more homogeneous in density than those of A. aculeatum, both from the internal to the external, and from the lower to the upper parts of the stem. Field estimates of stem growth rates revealed that A. maripa growth is also more constant through development in height. Short A. aculeatum palms had faster growth rates than A. maripa, as they get taller, stem growth rates are reduced and approach A. maripa rates. The difference could explain the numerical advantage of A. maripa over A. aculeatum at the typically open seasonally dry Amazonian forest. Advantage, which is probably reverted in favor of A. aculeatum at the dense forests of Central and Western Amazon. The study of A. maripa palms distribution in relation to forest disturbance suggests that, both natural and anthropic disturbance affects favorably their occurrence. However, due to the long time of palms development in relation to ordinary scientific research, the study of the importance of forest disturbance to the development of arborescent palms must consider the historical perspective and explicit variations of palms distribution across the landscape. The seeds of A. aculeatum are substantially larger that those of A. maripa and carry more reserves to the embryo. The study of the seed rain of both species, based in the seedling distribution patterns in relation to reproductive adults contradict general patterns among Angiosperms as, at the considered scale, the seeds of A. aculeatum, larger, were more homogeneously dispersed than the seeds of A. maripa. The result can be explained by the seed dispersal services paid by scatterhoarding caviomorph rodents (agoutis, Dasyprocta aguti). The rodents apparently prefer the nutrient richer seeds of A. aculeatum, being more efficient disperser to this palm, if compared with their behavior towards A. maripa, which pays smaller bites for the seed dispersal service. Hypotheses for the maintenance of tropical forest tree diversity were tested with a system that includes the palm Attalea maripa, the beetle Pachymerus cardo and vertebrate predators of large seeds in a palm patch and its adjacent forest in Southeastern Amazon. Seed predation was affected by host-specificity degree of the animals involved. Seed survivorship depended on the distance from the palm-patch but was unrelated to distance from individual fruiting palms. The result presented in the data chapters of this thesis suggests that the proposed model is appropriate and that its study is rewarding to the understating of the importance of large arborescent palms on the dynamics of seasonally dry Amazonian forests. As a result, highlights their role as tools for the environmental reconstitution in a likely future of larger scale deforestation in the Amazon.
Keywords: Florestas; Amazônia; Palmeiras brasileiras; Ecologia; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS